Certain topical aspects of the practical application of the laser microdissection technology for the purpose of forensic molecular-genetic analysis - Ivanov, P L; Leonov, S N; Zemskova, E Iu (Sudebno-meditsinskaia ekspertiza, 2012)
Experiments with the use of the laser capture microdissection (LCM) technology for the purpose of forensic molecular-genetic analysis carried out on real objects revealed a number of specific aspects of practical LCM application. Some of these problems have been investigated in the present work with special reference to the characteristics of the cells of interest and their physical properties in study objects. The data obtained give reason to conclude that a failure of genotyping of individual cells obtained by the LCM technique may be due to the lack of genetic material suitable for analysis. Another important cause is poor availability of the genetic material for PCR attributable to the resistance of cells subjected to the prolonged influence of environmental factors to thermal destruction. In order to obviate this difficulty, we developed a highly efficacious system with the use of PCR lysis reagents having the advantage of combination of proteolysis and the use of detergents compatible with PCR.